Modelos de crescimento de quatro espécies madeireiras de floresta de várzea da amazônia central por meio de métodos dendrocronológicos - Rosa, Sejana Artiaga (Instituto Nacional de Pesquisas da Amazônia - INPA, 2008)
Timber harvesting is an important economic activity in nutrient-rich floodplain forests (várzea) of Central Amazonia. In the Western Amazon basin of Brazil and Peru, access to terra firme forests is restricted due to the absence of a road network. Still, 60 90% of the local and regional markets are provided with timber obtained from the floodplain forests. Costs for logging are lower in the floodplain forests (US$ 6.73 m 3) as in the non-flooded terra firme forests (US$ 14.32 m 3) due to the easier access and lower energy costs. Timber harvesting is based on a forest management plan applying felling cycles of 25-35 year an diameter cutting limits of 50 cm. Tree-ring analysis (dendrochronology) is a powerful tool to determine tree ages and wood growth providing data for long-term growth patterns and forest dynamic as a basis for the development of sustainable forest management systems. This study aims to model growth patterns of Hura crepitans L. (Euphorbiaceae), Cedrela odorata L. (Meliaceae), Ocotea cymbarum Mez (Lauraceae), and Sterculia elata Ducke. (Malvaceae), tree species of commercial importance in the central Amazonian várzea. Based on the growth patterns species-specific felling cycles and minimum logging diameter are estimated to support the development of future management plans towards sustainability in the Mamirauá Reserve of Sustainable Development (MRSD). From every tree species tree heights and diameter at breast height ≥ 10cm were measured from 20 individuals. A total of 20 stem disks and 110 cores of 5 mm diameter were collected using an increment borer. The cores were progressively polished with sanding paper to describe and analyze wood anatomical patterns as a key for a successful dendrochronological study. The analyses were performed in the Dendrochronology Laboratory of INPA/Max-Planck project in Manaus. Tree age was determined by ring-counting and diameter increment rates were determined by ring-width measurements using a digital measuring device (LINTAB). Based on the data set of tree age, diameter and tree height, growth models were developed for each species based on significant age-diameter and diameter-height relationships to estimate volume growth. The diameter of the maximum current volume increment was defined as minimum logging diameter (MLD). The MLD of the studied tree species varied between 37,6 cm (C. odorata) and 128,8 cm (H. crepitans). The felling cycle was estimated by the mean passage time of 10 cm diameter classes until reaching the derived MLD. Felling cycles varied between 9,7 years (H. crepitans and S. elata) and 12,0 years (C. odorata), much lower than applied in the current management practices based on forest legislation and normative instruction of the Brazilian Environmental Agencies (IBAMA). The results indicate that current forest management practices are inefficient to manage the timber stocks of the studied commercial tree species. Management plans must consider species-specific growth rates to guarantee a sustainable forest management. vi
Keywords: Dendrocronologia; Anéis de crescimento; Florestas de várzea; Manejo florestal